Arc discharge plasma of carbon ion in H2 and air - Daud, Suzairi; Ahmad Noorden, Ahmad Fakhrurrazi; Aziz, Muhammad Safwan; Ali, Jalil (American Institute of Physics Inc., 2017)
Carbon nanostructures become more useful nowadays due to their unique carbon elements and advantages. This paper will present the determination of the energy of carbon ion in different environments and pressures. In this work, arc discharge plasma generated by graphite electrode were chosen to produce carbon nanostructures and CR-39 material were exposed to energetic carbon ion. It was etched with 6.25 M of NaOH solution for 8 hours in (72±1)°C temperature to remove the material from the tracks and the etched detectors will be analyzed with optical microscope. The energy of carbon ion obtained by observing and measured the ion track size on CR-39 target under optical microscope and calculated using the relevant formula. High values of carbon ions energy were observed in hydrogen environment as compared to air at the same pressure.